Applicaton of Nutrients on Growth of Acacia catechu in Nursery Bed - Raina, A. K.; Pharasi, S. C.; Prasad, K. G. (Indian Forester, 1990)
Experiment was laid out to know the effect of N, P and Zn on germination, survival and growth of Acacia catechu seedlings in nursery. Basal dose of chemical fertilizers decreased seed germination and survival. It was observed that 10 ml solution per bag of O.2% each of urea and superphosphate applied 10th and 13th week and 10 ml per bag of O.02% zinc sulphate solution applied 15th week after seed sowing increased the height growth of seedlings. Using this method, plantable seedlings were ready within 16 to 18 weeks of sowing directly in the polythene bags, thus saving time, money land and labour.